Multimodal Discourse Analysis of Figures Used in the English Textbook “Get Smart Plus” - Didin Nuruddin Hidayat; Khoirunnisa Fitri; Alek Alek; Nida Husna; Agus Sufyan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The study analyzed the multimodality of the EFL textbook for elementary school students. A qualitative descriptive study has been employed to carry out this study. The source of the data is the textbook, namely Get Smart Plus. The data was visual and verbal elements within the textbook, including any text and images that explain each other. The study used the multimodal framework proposed by Krees Van Leuween’s visual grammar and Halliday’s transitivity system to analyze the data. The finding shows that the visual elements of the textbook contain representation, composition, and relational patterns. In addition, the dominant process in the textbook is the verbal mode of communication (42%). However, the material process based on the analysis of Halliday’s theory was not represented in the book. The visual and verbal elements relate to each other and can potentially support students’ learning and understanding of the content. Therefore, the textbook can be a multimodal resource for students’ English learning. This study hopes to benefit textbook developers and designers by improving the use of visual and verbal elements of the textbook to support students’ cognitive development. Further research can be conducted on the impact of textbook multimodality on students’ learning achievement to contribute more to the study of discourse. Keywords: Multimodal Discourse Analysis, EFL, English textbook